Cyclo - Rossignon, Christophe; Trần, Anh Hùng 1962-; Lê, Văn Loc; Leung, Tony Chiu Wai 1962-; Trần, Nữ Yên Khê 1968- (Dreamix, 2004)
In the heart of Ho Chi Minh City, a young cyclo (pedicab driver) transports anonymous passengers through the teeming streets, trying to eke out a meager living for his two sisters and elderly grandfather